إسهام بيئة العمل الداخلية على القيادات الإدارية الجامعية - ناهي كعيد عباس (Journal of College of Education, 2019)
In this researcher the researcher aims to: 1- To have a clear Knowledge about high managers internal work environment, at sumer university. 2- Clarifies the relationship between the effective parameters of work environment. 3- To have a clear about work environment dimentions. Research methodology : The descriptive approach has been tackled in this research, because it qualifies the research methodology. The researcher used the questionnaire as a research tool. And he used the SPSS computer statistical programmer. The results of this research clarifies that clarifies that higher management suggestions serves the organizational framework. And encouraging all types of communication. And helping the head of departments to use all types of communication. And helping the heads of departments to use all types of encouragement.